Characterization, and crystal structure of thiophenyl-2-methylidene-2- aminophenol - Cuin, A.; Pereira, G. A.; Bortoluzzi, A. J.; Massabni, Antonio Carlos [UNESP]; Corbi, P. P. (Pleiades Publishing, 2013)
The Schiff base thiophenyl-2-methylidene-2-aminophenol (ImineOH) is obtained from a stoichiometric mixture of 2-thiophenecarboxaldehyde and 2-aminophenol in ethanol under reflux at 90 C. Its crystal structure is determined by single crystal X-ray diffraction. ImineOH packs in an orthorhombic unit cell in the Pbca space group with the unit cell parameters a = 16.942(4) Å, b = 13.4395(11) Å, and c = 17.5857(12) Å, V = 4004.1(10) Å3, Z = 16. Strong hydrogen bonds are present in the ImineOH structure. Apart from the X-ray study, ImineOH was characterized by elemental analysis (CHN-S) and FT-IR (4000 cm-1 to 400 cm-1), UV-Vis and 13C, 1H, and 15N NMR spectroscopic measurements. © 2013 Pleiades Publishing, Ltd.
Keywords: 2-aminophenol; 2-thiophenecarboxaldehyde; Schiff base; thiophenyl-2-methylidene-2-aminophenol